2018
DOI: 10.1002/pi.5537
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of silver/reduced graphene oxide/chitosan colloid and application of the nanocomposite in antibacterial and catalytic activity

Abstract: Reduced graphene oxide (RGO) decorated with silver nanoparticles (AgNPs) was synthesized by a facile solution‐based approach in chitosan (CS) solution. The morphology and elemental composition of as‐prepared Ag/RGO/CS colloid were characterized by SEM and energy dispersive X‐ray spectroscopy, respectively. TEM images show that most of the AgNPs are uniformly dispersed in the CS matrix while the other nanoparticles are decorated on the RGO nanosheets. XRD indicates that the interlayer distance of RGO is between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 62 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Figure 2(c), SEM-mapping, illustrates that the formed membrane has a gap between particles with a high density, indicating a large surface area of the membrane formed. Based on the morphology of the synthesized membrane, the research reported by An et al, (2018) indicates that the morphology of Ag/rGO/CS colloids is very dense and has a large surface area. The large surface area and contact area of the synthesized membrane affect the bonding power between the matrix and filler and cause an increase in the contact between the transducer and the enzyme as a biological element, resulting in effective adsorption of the target molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2(c), SEM-mapping, illustrates that the formed membrane has a gap between particles with a high density, indicating a large surface area of the membrane formed. Based on the morphology of the synthesized membrane, the research reported by An et al, (2018) indicates that the morphology of Ag/rGO/CS colloids is very dense and has a large surface area. The large surface area and contact area of the synthesized membrane affect the bonding power between the matrix and filler and cause an increase in the contact between the transducer and the enzyme as a biological element, resulting in effective adsorption of the target molecule.…”
Section: Resultsmentioning
confidence: 99%
“…AgNPs are tightly connected to the CS OH groups, forming a network of polymeric chains that reduces NP aggregation and boosts stability (Kumar, 2000). Due to CS's antibacterial capabilities, the combination with AgNPs increased its effectiveness (An et al, 2018). In this study, silver nitrate was biologically reduced with E. coli D8 cell-free supernatant to biosynthesize AgNPs, which were then alternatively integrated into a chitosan matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The major phenolic compounds of licorice include glycosides of liquiritigenin (4,7-dihydroxyflavanone) and isoliquiritigenin (2,4,4-trihydroxychalcone) (Bethapudi et al, 2022). Licorice extract has been investigated as a substitute to bismuth that is normally used in quadruple therapy (Li et al, 2018). Bismuth protects against acid and pepsin secretions by covering the location of the lesion and promoting mucous secretion (Sreeja et al, 2020).…”
Section: Introductionmentioning
confidence: 99%